Correction: On the electronic structure and hydrogen evolution reaction activity of platinum group metal-based high-entropy-alloy nanoparticles. Issue 20 (14th May 2021) - Wu, Dongshuang; Kusada, Kohei; Yamamoto, Tomokazu; Toriyama, Takaaki; Matsumura, Syo; Gueye, Ibrahima; Seo, Okkyun; Kim, Jaemyung; Hiroi, Satoshi; Sakata, Osami; Kawaguchi, Shogo; Kubota, Yoshiki; et al.
Abstract : Correction for 'On the electronic structure and hydrogen evolution reaction activity of platinum group metal-based high-entropy-alloy nanoparticles' by Dongshuang Wu et al., Chem. Sci., 2020, 11, 12731–12736, DOI: ; 10.1039/D0SC02351E .